Horizontal Tourism Coopetition Strategy for Marketing Performance – Evidence From Theme Parks - Wu, Meiju; He, Jianmin (Frontiers in Psychology, 2022)
Unprecedentedly impacted by COVID-19, tourism enterprises are pushed to adopt new strategic management to cope with the changes of tourists’ consumer perception for sustainable development, such as corporate and compete simultaneously with their competitors. Our study aims to investigate the intermediate role of coopetition including the three dimensions of resource similarity, market commonality and willingness to cooperate in the marketing and performance relationship. Primary data on 360 observers was collected via questionnaire distribution to theme park managers in China with 85.3% accuracy in response rate. Structural equation modeling (SEM) was used to verify the intermediate effect of coopetition on marketing performance in tourism enterprises. The results of SEM indicate 1) the intermediate role of tourism coopetition including the three dimensions existing in the relationship between tourism marketing and performance, 2) more significant positive impact on non-financial performance than it on financial performance, 3) the mechanism of implementing coopetition. This study gives the supportive evidence for tourism enterprises to implement coopetition and highlights the implications for appropriately developing coopetition strategies and tactics to achieve the synergy effect for the individual enterprises and the spillover effect for the destination regarding policy making, mindset and partner selection.